Tinjauan Pedagogi Biologi Berbasis Kearifan Lokal Naniura-Sashimi Batak: (Review of Biology Pedagogy Based on Local Wisdom of Naniura-Sashimi Batak) - Silaban, Oky Rizkiana; Sriyati, Siti (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Biology learning is abstract, universal, monotonous, and less relevant to everyday life, thus causing the learning process to become less meaningful. Meaningful learning is integrating learning to facts in everyday life and learns the meaning of science for life. In line with the demands of an independent curriculum, which expects a learning process that is contextual and touches on and answers local problems from the surrounding area, The solution that can answer this problem is a locally-based learning approach that is integrated into biology lessons. The purpose of this article is to examine the local wisdom of Naniura-Sashimi Batak in biology learning. The research method used is a literature study by reviewing national and international journals related to the Local Wisdom of Naniura-Sashimi Batak and its relationship to biology lessons. Integrate into learning by mapping community science and scientific science as well as relationships in biological material. abstrak. Pembelajaran biologi bersifat abstrak, universal, monoton, dan kurang relevan dengan kehidupan sehari-hari, sehingga menyebabkan proses pembelajaran menjadi kurang bermakna. Pembelajaran yang bermakna adalah mengintegrasikan pembelajaran dengan fakta-fakta dalam kehidupan sehari-hari dan mempelajari makna ilmu pengetahuan untuk kehidupan. Sejalan dengan tuntutan kurikulum mandiri, yang mengharapkan proses pembelajaran yang kontekstual dan menyentuh serta menjawab masalah-masalah lokal dari sekitar, Solusi yang dapat menjawab masalah ini adalah pendekatan pembelajaran berbasis lokal yang terintegrasi ke dalam pelajaran biologi. Tujuan dari artikel ini adalah untuk mengkaji kearifan lokal Naniura-Sashimi Batak dalam pembelajaran biologi. Metode penelitian yang digunakan adalah studi literatur dengan meninjau jurnal-jurnal nasional dan internasional yang terkait dengan Kearifan Lokal Naniura-Sashimi Batak dan hubungannya dengan pelajaran biologi. Terintegrasi dalam pembelajaran dengan memetakan ilmu komunitas dan ilmu sains serta hubungannya dalam materi biologi.